Influence factors analysis of flow-induced vibration of elbow in piping system - KE Bing (Zhongguo Jianchuan Yanjiu, 2018)
[Objectives] As important parts of any piping system, the elbows are one of the main factors causing vibration. To have a better understanding of Flow-Induced Vibration(FIV) of elbows in piping system.[Methods] In this paper, the diameter, curvature radius, bending angle are chosen as variables, and a study of turbulence flow-induced vibration of elbow by a combined method of finite element numerical calculation and experiment is carried out, so as to obtain the effect of different curvature radius, bending angle on the fluctuating pressure and the structural vibration response of pipeline elbow under variable flow velocity.[Results] The numerical and experimental results show that the effect of the curvature radius and flow velocity on the FIV of an elbow is significant; with the increase of the curvature radius and decrease of flow velocity, the FIV decreases.[Conclusions] The research results of this paper can provide useful references for the acoustic design of piping systems.